Global Humanitarian Overview 2023 - United Nations Office for the Coordination of Humanitarian Affairs (United Nations, 2022)
A snapshot of the global trends driving increased humanitarian needs in 2023, analysis from 2022 and an overview of where the system is delivering better to help those affected by crises. The Global Humanitarian Overview (GHO) is the world’s most comprehensive, authoritative and evidence-based assessment of humanitarian need. Through plans that prioritize those most in need, it aims to fight hunger, killer diseases, gender-based violence and displacement.